HENMT1 is involved in the maintenance of normal female fertility in the mouse. (30th September 2021) - Hutt, Karla J; Lim, Shu Ly; Zhang, Qing-Hua; Gonzalez, Maria; O'Connor, Anne E; Merriner, D Jo; Liew, Seng H; Al-Zubaidi, Usama; Yuen, Wai Shan; Adhikari, Deepak; Robker, Rebecca L; Mann, Jeffrey R; et al.
Abstract: PIWI-interacting small RNAs (piRNAs) maintain genome stability in animal germ cells, with a predominant role in silencing transposable elements. Mutations in the piRNA pathway in the mouse uniformly lead to failed spermatogenesis and male sterility. By contrast, mutant females are fertile. In keeping with this paradigm, we previously reported male sterility and female fertility associated with loss of the enzyme HENMT1, which is responsible for stabilising piRNAs through the catalysation of 3′-terminal 2′- O -methylation. However, the Henmt1 mutant females were poor breeders, suggesting they could be subfertile. Therefore, we investigated oogenesis and female fertility in these mice in greater detail. Here, we show that mutant females indeed have a 3- to 4-fold reduction in follicle number and reduced litter sizes. In addition, meiosis-II mutant oocytes display various spindle abnormalities and have a dramatically altered transcriptome which includes a down-regulation of transcripts required for microtubule function. This down-regulation could explain the spindle defects observed with consequent reductions in litter size. We suggest these various effects on oogenesis could be exacerbated by asynapsis, an apparently universal feature of piRNA mutants of both sexes. Our findings reveal that loss of the piRNA pathway in females has significant functional consequences.